AKAD DALAM TRANSAKSI EKONOMI SYARIAH - Urbanus Uma Leu (TAHKIM, 2017)
Akad has significance meaning in the community lives. In the economical concept, human life in a group of communities that entirely established the system. The economic system is interaction of the smallest units (consumers and producers) into larger economic units in a particular region. The strength of interaction pattern of economic units is most determined by the accompanying akad. The akad facilitate each person who undergoing economic activity, including goods and services. In this regard the procurement activity (production), dissemination/sharing (distribution), and consumption, is a number of human behavior is most determined by the accompanying contract. Key words: Akad, transaction, Islamic economy.